Myeloid cell ACE shapes cellular metabolism and function in PCSK-9 induced atherosclerosis - Cao, DuoYao; Saito, Suguru; Xu, LiMin; Fan, Wei; Li, Xiaomo; Ahmed, Faizan; Jovanovic, Predrag; Shibata, Tomohiro; Che, Mingtian; Bernstein, Ellen A.; Gianni, Jorge; Divakaruni, Ajit S.; et al. (Frontiers in Immunology, 2023)
The pathogenesis of atherosclerosis is defined by impaired lipid handling by macrophages which increases intracellular lipid accumulation. This dysregulation of macrophages triggers accumulation of apoptotic cells and chronic inflammation which contributes to disease progression. We previously reported that mice with increased macrophage specific angiotensin converting enzyme, termed ACE10/10 mice, resist atherosclerosis in an adeno-associated virus-proprotein convertase subtilisin/kexin type 9 (AAV-PCSK9) induced model. This is due to increased lipid metabolism by macrophages which contributes to plaque resolution. However, the importance of ACE in peripheral blood monocytes, which are the primary precursors of lesional infiltrating macrophages, is still unknown in atherosclerosis. Here, we show that the ACE-mediated metabolic phenotype is already triggered in peripheral blood circulating monocytes and that this functional modification is directly transferred to differentiated macrophages in ACE10/10 mice. We found that Ly-6Clo monocytes were increased in atherosclerotic ACE10/10 mice. The monocytes isolated from atherosclerotic ACE10/10 mice showed enhanced lipid metabolism, elevated mitochondrial activity, and increased adenosine triphosphate (ATP) levels which implies that ACE overexpression is already altered in atherosclerosis. Furthermore, we observed increased oxygen consumption (VO2), respiratory exchange ratio (RER), and spontaneous physical activity in ACE10/10 mice compared to WT mice in atherosclerotic condition indicating enhanced systemic energy consumption. Thus, ACE overexpression in myeloid lineage cells modifies the metabolic function of peripheral blood circulating monocytes which differentiate to macrophages and protect against atherosclerotic lesion progression due to better lipid metabolism.